Economic and racial inequalities in the prenatal care of pregnant teenagers in Brazil, 2011-2012 - André Henrique do Vale de Almeida; Silvana Granado Nogueira da Gama; Maria Conceição Oliveira Costa; Elaine Fernandes Viellas; Katrini Guidolini Martinelli; Maria do Carmo Leal
Abstract Objectives: to analyze the prenatal care of pregnant teenagers interviewed in the post-partum period in Brazilian maternity hospitals, according to economic status and skin color. Methods: data were obtained from the Birth in Brazil study, a national hospital-based survey in 2011 and 2012. Information was obtained from interviews with the postpartum women and from data collected from their prenatal cards. Multivariate logistic regression was used to verify whether maternal and prenatal care characteristics were associated with ina-dequate prenatal care. Results: a total of 3,317 teenage mothers were interviewed in the postpartum period, 84.4% of whom had received inadequate prenatal care, with worse results for lower-income, lower-schooling, and multiparous teens. In the same way, it became evident the higher proportion of black teenagers and those from economic classes D/E among those who failed to receive routine laboratory tests, who received little orientation on the pregnancy, labor, and childbirth, and who were forced to go from one maternity hospital to another before being admitted to give birth. Conclusions: strategies targeted to the most vulnerable pregnant teenagers should be implemented in order to achieve greater equality in teenagers' prenatal care, seeking to assure easier access, earlier initiation of care, and greater case-resolution capacity